Recuperação de platina de eletrodos de células a combustível de membrana trocadora de prótons - Sampaio, André Mychell Barbieux Silva (2017)
The used platinum in proton exchange membrane fuel cell electrodes (PEMFC) was recovered by oxidation at high temperature using a muffle. Four materials with initial masses of 38.72 grams were prepared. The material was oxidized by acid and then the platinum concentration was determined by the atomic absorption method. Soon after, by reduction by sodium borohydride, the obtained metal was reduced to metal platinum on a carbon surface with high surface area. The material, after filtration and drying, was characterized by X-ray diffraction. The activity for electro-oxidation of hydrogen was evaluated by cyclic voltammetry in 0.5 mol.L -1 sulfuric acid and in acid solution containing 0,8 mol.L -1 of ethanol. For evaluation of the stability of the material formed chronoamperometry at several potentials for 600 s.